Graphene coated photonic crystal fiber biosensor based on surface plasmon resonance - Paul, Alok Kumar; Sarkar, Ajay Krishno; Razzak, S. M. Abdur (2017 IEEE Region 10 Humanitarian Technology Conference (R10-HTC), 2017)
This paper presents a graphene coated photonic crystal fiber (PCF) biosensor based on surface plasmon resonance (SPR). A full-vectorial finite element method (FEM) with perfectly matched boundary is used as mode solver to investigate the performance of the proposed biosensor. In the proposed SPR based PCF biosensor, plasmonic material and sensing layer is placed on the outer surface to meet the fabrication challenge. The proposed SPR based PCF biosensor exhibits the wavelength sensitivity of 8500 nm/RIU for both x- and y-polarization, amplitude sensitivity of 3961.2 RIU −1 for x-polarization and 5645.4 RIU −1 for y-polarization, sensor resolution of 1.18∗ 10 −5 RIU with the sensing ranges from analyte refractive index (RI) of 1.36 to 1.4. Considering high sensitivity and high sensor resolution, this proposed SPR based PCF biosensor can be a promising candidate for unknown analyte detection.